2016
DOI: 10.3346/jkms.2016.31.s1.s75
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Clinical Cancer Radiotherapy: Concerns Regarding Normal Tissue Protection and Quality Assurance

Abstract: Radiotherapy, which is one of three major cancer treatment methods in modern medicine, has continued to develop for a long period, more than a century. The development of radiotherapy means allowing the administration of higher doses to tumors to improve tumor control rates while minimizing the radiation doses absorbed by surrounding normal tissues through which radiation passes for administration to tumors, thereby reducing or removing the incidence of side effects. Such development of radiotherapy was accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The field of radiation oncology has rapidly evolved over the last three decades due to the advances in diagnostic radiology that allows for better tumor volume definition during treatment planning, and the development of new irradiation techniques such as intensity‐modulated radiotherapy (IMRT) and stereotactic body radiation therapy (SBRT), making possible a better optimization of dose distribution around the planning target volume (PTV) (1) . Those advanced techniques require a high and verified accuracy in dose calculation to ensure that the prescribed dose is actually delivered to the tumor with good sparing of the surrounding normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The field of radiation oncology has rapidly evolved over the last three decades due to the advances in diagnostic radiology that allows for better tumor volume definition during treatment planning, and the development of new irradiation techniques such as intensity‐modulated radiotherapy (IMRT) and stereotactic body radiation therapy (SBRT), making possible a better optimization of dose distribution around the planning target volume (PTV) (1) . Those advanced techniques require a high and verified accuracy in dose calculation to ensure that the prescribed dose is actually delivered to the tumor with good sparing of the surrounding normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…These tumours, induced via radiotherapy, mostly arise with a latency of at least 5-10 years [59,60] The toxicity of RT can be reduced through dose reductions, volume reductions, and the optimization of using IMRT (intensity-modulated radiotherapy). IMRT and VMAT (volumetric modulated arc therapy) are more effective than 3D-CRT in terms of target coverage, dose homogeneity, and reducing toxicity to normal organs [61][62][63]. IMRT/VMAT techniques were not available at the time at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…However, a paradigm shift has occurred in the field of RT, spurred by technological advancements that allow for precise tumor targeting and the delivery of a higher biological RT dose to the tumor, while sparing normal tissues. This represents a significant improvement over past methods [15]. Ning et al [16] studied 2 human RCC cell lines (Caki-1 and A498) and reported that the α/β ratio of RCC cells ranged from 2.6 to 6.9 Gy, which is lower than the dose delivered to most radiosensitive tumor types (α/β ratio of approximately 10 Gy).…”
Section: Radiosensitivity Of Rccmentioning
confidence: 98%